Discrepancy of blood pressure between limbs bilateral subclavian artery stenosis: a case report - Ravichandran, Arvindraj; Anand, N. N.; Ramalingam, A. Karthick; Mohan, Anandh (International Journal of Advances in Medicine, 2022)
Bilateral subclavian artery stenosis is a rare condition which usually presents with claudication pain associated with severe cardiac complications. Here we describe a rare case of asymptomatic bilateral subclavian artery stenosis. On examination, the patient was drowsy, dehydrated, and hypotensive, with evidence of DKA, for which the patient was treated, but the hypotension was persistent, with blood pressure in the lower limb more than that of the upper limb. A complete examination was done, and the USG neck and CT Aortogram showed retrograde flow in the left vertebral artery, increased flow velocity in the subclavian artery and filling defect in the bilateral subclavian artery, respectively. Thus, bilateral subclavian artery stenosis was diagnosed and treated accordingly.